ARAH BARU EPISTEMOLOGI PEMIKIRAN ISLAM: PARADIGMA INTEGRASI-INTERKONEKSI M. AMIN ABDULLAH - Junaidi Junaidi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Integration-Interconnection is a scientific paradigm that is offered by M. Amin Abdullah to the Islamic world, especially Islamic scholar world. As one effort raised to respond nowadays global reality. It can also be called as an effort to make Islamic scholarship relevant to the world dynamics. This paradigm have an ideal concept in a Spider Web metaphorical form. And in somewhat contextual way, this paradigm is well applied in Universitas Islam Negeri Sunan Kalijaga Yogyakarta.